Learning while Playing: Effective Strategies for Strengthening the Character of Elementary School Students in Sidrap Regency - Hermansyah, Sam; Mohamed, S. H. Sheik; Nirmala, M. (Civitas : Jurnal Pengabdian Masyarakat, 2024)
An early age. This study explores the implementation of the Learning While Playing method as an effective strategy for strengthening character education among elementary school students in Sidrap Regency. Through interactive and engaging learning activities, students are encouraged to develop positive values such as discipline, cooperation, responsibility, and critical thinking. The research was conducted through direct implementation in elementary schools, where students participated in various games and activities designed to instill moral and ethical principles. The findings indicate that the Learning While Playing approach not only enhances students' enthusiasm and engagement in the learning process but also fosters better character development in a natural and enjoyable manner. This method is recommended as an alternative educational strategy to cultivate strong character traits in young learners.